Tuệ Tĩnh 1330-?" - Thompson, C Michele (Dictionary of Medical Biography, 2007)
Keywords: dept.his

Lán Ông 1721-1791? - Thompson, C Michele (Dictionary of Medical Biography, 2007)
Keywords: dept.his

Review of Views of Seventeenth-Century Vietnam: Christoforo Borri on Cochinchina and Samuel Baron on Tonkin - Thompson, C. Michele (Crossroads: An Interdisciplinary Journal of Southeast Asian Studies, 2007)
Keywords: book.review; dept.his

Not Your (founding) Fathers' Constitution: Teaching United States Constitutional History - Gerber, Richard A. (The Connecticut Urban Consortium ; New Haven Public Schools, 2007)
Synopsis of the lectures presented during the three-year program, together with a PowerPoint presentations on CD-ROM. This material can be used for preparation of classroom instructional program or directly in the classroom.
Keywords: History; Study and teaching; Study and teaching; Constitutional history; United States. Constitution; United States; United States; dept.his; faculty_collection

When France Was King of Cartography: The Patronage and Production of Maps in Early Modern France - Petto, Christine Marie (Lexington Books, 2007)
When France Was King of Cartography investigates over a thousand maps and nearly two dozen map producers, analyzes the map as a cultural artifact, map producers as a group, and the array of map viewers over the course of two centuries in France. The book focuses on situated knowledge or 'localized' interests reflected in these geographical productions. Through the lens of mapmaking, it examines the relationship between power and the practice of patronage, geography, and commerce in early modern France.
SCSU Faculty Scholar Award
Keywords: 17th century; Cartography; 17th century; Map industry and trade; 18th century; 18th century; Map industry and trade; Cartography; France; History; SCSU Faculty Scholar Award; award_winner; dept.his

Crisis of the Black Intellectual - Wright, W. D. (Third World Press, 2007)
Keywords: African American intellectuals; African Americans; Intellectual life; dept.his; faculty_collection

"I should not be wearing a pilgrim hat": Making an Indian place in urban schools, 1945-75 - Amerman, S. (American Indian Culture and Research Journal, 2007)
2 citations (Crossref) [2023-10-31]
Keywords: dept.his

The Missouri Compromise and Its Aftermath: Slavery and the Meaning of America - Forbes, Robert P. (University of North Carolina Press, 2007)
Robert Pierce Forbes goes behind the scenes of the crucial Missouri Compromise, the most important sectional crisis before the Civil War, to reveal the high-level deal-making, diplomacy, and deception that defused the crisis, including the central, unexpected role of President James Monroe. Although Missouri was allowed to join the union with slavery, the compromise in fact closed off nearly all remaining federal territories to slavery.When Congressman James Tallmadge of New York proposed barring slavery from the new state of Missouri, he sparked the most candid discussion of slavery ever held in Congress. The southern response quenched the surge of nationalism and confidence following the War of 1812 and inaugurated a new politics of racism and reaction. The South's rigidity on slavery made it an alluring electoral target for master political strategist Martin Van Buren, who emerged as the key architect of a new Democratic Party explicitly designed to mobilize southern unity and neutralize antislavery sentiment. Forbes's analysis reveals a surprising national consensus against slavery a generation before the Civil War, which was fractured by the controversy over Missouri.
Keywords: dept.his

Technology and the culture of modernity in Britain and Germany 1890-1945. - Paddock, Troy (German studies review, 2007)
tex.unique-id: ISI:000244426200049
Keywords: dept.his; ⛔ No DOI found